Երկրորդային հումքից մրգաբանջարեղենային փոշիների ստացման մեթոդներիմշակում և օգտագործում ալրային հրուշակեղենի արտադրությունում - Յավրույան, Ն. Վ.; Կարապետյան, Վ. Ա.; Գոմցյան, Ե. Խ.; Միրումյան, Ի. Ա. (ՀԱԱՀ հիմնադրամ)
Ներկայումս մեծ ուշադրություն է դարձվում բնակչության սննդակարգի խախտումներին, մասնավորապես կենդանական ճարպերի չափից ավելի, չհագեցած ճարպաթթուների, վիտամինների և սննդային մանրաթելերի ոչ բավարար օգտագործմանը: Հրուշակեղենային արտադրանքի պահանջարկը մշտապես աճում է, ուստի խնդիր է դրվել հետազոտությամբ հիմնավորել առաջին մզվածքի մրգաբանջարեղենային հյութերից ստացված երկրորդային հումքի կիրառումը կեքսերի արտադրությունում։ Մրգային և բանջարեղենային փոշիների օգտագործումը հնարավորություն կտա ընդլայնել ալրային հրուշակեղենի տեսականին, պատրաստի արտադրանքը հարստացնել սննդային մանրաթելերով ու վիտամիններով։ В настоящее время большое внимание уделяется проблемам пищевого рациона населения, в частности избыточному приему животных жиров и недостаточному потреблению ненасыщенных жирных кислот, витаминов и пищевых волокон. Спрос на кондитерские изделия постоянно растет, поэтому была поставлена задача путем исследования обосновать применение вторичного сырья, полученного из фруктовых и овощных соков первого отжима, в производстве кексов. Использование фруктовых и овощных порошков позволит расширить ассортимент мучных кондитерских изделий, обогатить готовое изделие пищевыми волокнами и витаминами. The demand for confectionery products is constantly growing, so a task has been set up to justify the use of secondary raw materials obtained from the first extract fruit and vegetable juices in the production of cupcakes. The use of fruit and vegetable powders will enable to expand the product range of flour confectionery, as well as to enrich the finished product with dietary fibers and vitamins. Apple and parsnip pulp were subjected to primary research, and their nutritional value was determined. The chemical and vitamin indicators of the finished products were determined according to the research methods regulated by GOST. Then, comparative evaluation of the vitamin value of apple and parsnip pulps was made. According to research results, fruit and vegetable pulp is not inferior in nutritional value to the original raw material, only certain losses occur during juice extraction process. In order to obtain fruit and vegetable powders and possibly preserve their valuable components, the convectivemicrowave drying method was used, which prevents microbial spoilage and deactivation of enzymes in the pulp. After drying, the content of vitamins, chemical and mineral substances in the obtained powders was studied. The addition of 10-15 % fruit and vegetable powders in the production recipe of cupcakes improves the physicochemical indicators of the finished product. Cupcakes made with the supplementation of fruit and vegetable powders also have a low energy value and contain a large amount of pectin substances. Therefore, we recommend using these powders in the manufacture of other products as well.
Keywords: Սննդագիտություն և տեխնոլոգիա